2023
DOI: 10.3390/gels9040334
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Dose Rate Effect in Tetrazolium Gellan Gel Dosimeters

Abstract: Tetrazolium salts provide an appealing candidate for 3D gel dosimeters as they exhibit a low intrinsic color, no signal diffusion and excellent chemical stability. However, a previously developed commercial product (the ClearView 3D Dosimeter) based on a tetrazolium salt dispersed within a gellan gum matrix presented a noticeable dose rate effect. The goal of this study was to find out whether ClearView could be reformulated in order to minimize the dose rate effect by optimizing of the tetrazolium salt and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The reconstruction techniques and parameters have been fully described elsewhere. 4,5 The 3D gamma analysis between the eclipse predicted and DLOS measured optical-CT dose distributions was performed by adapting the process detailed by Kevin Alexander utilizing 3D Slicer. 15 Figures 4 and 5 show dosimeter reconstruction, registration, and 3D Slicer volumes.…”
Section: D Dosimetry Readout Optical Ct Scanning and Analysis Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The reconstruction techniques and parameters have been fully described elsewhere. 4,5 The 3D gamma analysis between the eclipse predicted and DLOS measured optical-CT dose distributions was performed by adapting the process detailed by Kevin Alexander utilizing 3D Slicer. 15 Figures 4 and 5 show dosimeter reconstruction, registration, and 3D Slicer volumes.…”
Section: D Dosimetry Readout Optical Ct Scanning and Analysis Techniquementioning
confidence: 99%
“…INTRODUCTION ClearView (ModusQA) is a novel single use radiochromic gel dosimeter designed for use with optical CT for relative dosimetry measurements with several published accounts of use. [1][2][3][4][5][6] When exposed to ionizing MV radiation, ClearView gel changes color from optically clear to purple through the reduction of a water-soluble tetrazolium salt into an insoluble formazan dye. Independent studies 1,2,4 and the User's Guide 7 have reported the change in optical attenuation to be linear with dose between 0 and 80 Gy, with negligible signal diffusion and change with time (aging of irradiated gel ∼3 × 10 −4 cm −1 /day), low optical scattering component, and near tissue equivalence (electron density 1.015 ± 0.3% relative to water).…”
mentioning
confidence: 99%